Consumption of elicited soybean sprout flour increases calcium level in serum of ovariectomized rats - Aminah, Siti; Suparmo, Suparmo; Naruki, Sri; Wuryastuty, Hastari (Universa Medicina, 2017)
BackgroundThe decline in estrogens could lead to an imbalance of bone formation and absorption as well as bone mineralization. Phytoestrogens are known to have the potential to maintain bone health. Calcium and phosphorus are essential components for bone mineralization. This study aimed to investigate the effect of soybean sprout flour consumption on serum calcium and phosphorus levels in ovariectomized rats.MethodsA randomized post-test-only control group design involving 25 female Sprague-Dawley rats aged 2 months, which were divided into five groups: (i) normal controls on standard feed diet AIN-93 (C-N), (ii) ovariectomy controls on standard feed diet (OVX -N); (iii) ovariectomized rats on standard feed diet + ethinylestradiol (OVX -E), (iv) ovariectomized rats on standard feed diet + soybean flour (OVX -S); (v) ovariectomized rats on standard feed diet + soybean sprout flour (OVX -SS). The rats were treated for 6 weeks, then on the last day of treatment blood sampling was conducted. Analysis of calcium and phosphorus in serum was performed using the Arsenazo III photometric method. Data were analyzed using one-way Anova.ResultsMean serum calcium level was highest in the OVX-SS group (12.59 mg/dL Â± 1.32), while mean serum phosphorus level was highest in the C-N group (1.708 mg/dL Â± 0.28). Soybean sprout flour consumption had a significant effect on serum calcium levels (p=0.019), yet it had no effect on body weight and serum phosphorus levels of the rats.ConclusionConsumption of soybean sprout flour could positively affect serum calcium levels in rats.